National report on the status of women in Trinidad and Tobago (Ministry of Community Development Culture and Women'sAffairs Port of SpainTT, 1994)
Reviews and appraises at the national level, the situation in the early eighties and the changes since then. Reviews and appraises international support and technical assistance from international agencies to the Women's Affairs Division and local NGOs.
Bibliography: p. 41. Prepared for inclusion in the CARICOM sub-regional report